Order in international Finance, the promotion of IMF Stand-By Arrangements, and the Drafting of Priv Loan Agreements. (Pamphlet Series, 1982)
This paper discusses the promotion of IMF Stand-By Arrangements (SBAs), the drafting of private loan agreements, and order in international finance. The IMF approves a SBA or an extended arrangement for the benefit of a member country of the IMF only if the member presents to the IMF a letter of intent in which it sets forth a program of financial and economic adjustment that is likely to solve a present, or to fend off a possible balance-of-payments or reserve problem. A purchase is made in return for the purchasing member's currency. An extended arrangement is a variant that is in use for the purposes of a particular policy of the IMF.